Behavior of circular skirted footing on gypseous soil subjected to water infiltration - Aljuari Khawla A.; Fattah Mohammed Y.; Alzaidy Mohammed N. J. (Journal of the Mechanical Behavior of Materials, 2023)
Skirted footings are used to increase the final carrying capacity of shallow foundations resting on unstable soil and to decrease settling by limiting the soil beneath them. Skirted footings are utilized as an alternative to pile driving in poor strength soils at the top layer, such as gypseous soil, to save project costs and time spent installing piles while maintaining excellent performance. The settling of circular skirted footings resting on gypseous soil subjected to loading, infiltration, and collapsing stages was investigated using numerical calculations in this research study to determine their stability under environmental loadings. Finite element analyses were carried out using the commercially available software GEO-STUDIO. The stage of gypseous soil and variable skirt depth to footing diameter ratios (d/D) were taken into consideration. The findings reveal that both the soil stage and the skirt embedment ratio have a substantial impact on the ultimate bearing capacity and the settlement of weak soil, with the skirt embedment ratio increasing resulting in superior skirted footing performance. Furthermore, the improvement in settlement for the loading stage is the smallest, whereas the value for the collapsing soil stage is the largest.